2013
DOI: 10.5649/jjphcs.39.375
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ester Prodrugs with Magnesium Oxide Using the Simple Suspension Method

Abstract: The simple suspension method is a method of administering drugs via a feeding or gastrostomy tube, and it involves allowing tablets or capsules to be disintegrated and suspended in warm water at 55℃ without crushing. The present study evaluated the stability of two prodrugs suspended alone or in combination with an alkaline agent according to the simple suspension method. The study used two ester-prodrugs, acemetacin (AMT) and cefpodoxime proxetil (CPP), which are hydrolyzed at higher pH. Drug concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Aoki et al [ 15 ] reported that no degradation occurred in the co-suspension of MgO and clopidogrel bisulfate, which has an ester moiety. On the contrary, Suryani et al [ 16 ] reported that when ester prodrugs, acemetacin and cefpodoxime proxetil, were subjected to the SSM with MgO, the ester bonds were hydrolyzed. These chemical changes were considered to be serious because of the potential occurrence of gastrointestinal injury or some reduction of drug efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Aoki et al [ 15 ] reported that no degradation occurred in the co-suspension of MgO and clopidogrel bisulfate, which has an ester moiety. On the contrary, Suryani et al [ 16 ] reported that when ester prodrugs, acemetacin and cefpodoxime proxetil, were subjected to the SSM with MgO, the ester bonds were hydrolyzed. These chemical changes were considered to be serious because of the potential occurrence of gastrointestinal injury or some reduction of drug efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the stability of drugs by examining the changes following simultaneous suspension with alkaline drugs, such as magnesium oxide (MgO), or under pH-altered conditions [ 4 8 ]. Therefore, when multiple drugs are suspended together, attention should be paid to the suspension pH and changes after mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Yano et al 8) confirmed that 8 types of suspended drugs, including phenytoin and digoxin, were found to be stable. Suryani et al 9) demonstrated that suspended ester prodrugs (acemetacin, cefpodoxime proxetil)…”
Section: Introductionmentioning
confidence: 99%